The association of cancer‐related fatigue with all‐cause mortality of colorectal and endometrial cancer survivors: Results from the population‐based PROFILES registry. (22nd April 2019) - Adam, Salome; van de Poll‐Franse, Lonneke V.; Mols, Floortje; Ezendam, Nicole P. M.; de Hingh, Ignace H. J. T.; Arndt, Volker; Thong, Melissa S. Y.
Abstract: Purpose: Cancer‐related fatigue (CRF) is one of the most prevalent symptoms experienced by cancer survivors. However, researchers are only beginning to elucidate the risk factors, underlying mechanism(s), and its association with other outcomes. Research on the association between CRF and mortality is limited. Methods: The study sample comprised 2059 short‐term (<5 years postdiagnosis) cancer survivors from four PROFILES registry studies. Survivors diagnosed with stage I‐III colorectal cancer (CRC) or stage I‐III endometrial cancer (EC), with no evidence of disease, were identified and followed‐up by the Netherlands Cancer Registry. Fatigue was assessed with the Fatigue Assessment Scale. Cox proportional hazards models adjusted for demographic, clinical, and lifestyle characteristics were performed to assess the association of CRF with all‐cause mortality. Date of censoring was February 1, 2017. Results: Prevalence of CRF varied between 35.8% (male CRC) and 43.6% (female CRC). After a median follow‐up period of 9.0 years, a total of 408 survivors (20%) had died. CRF was associated with increased all‐cause mortality in male CRC survivors (HRadj = 1.75, 95% CI [1.31‐2.33]). This association remained statistically significant after excluding survivors experiencing anhedonia. For female CRC (HRadj = 1.32, 95% CI [0.90‐1.97]) and EC (HRadj = 1.27, 95% CI [0.84‐1.90]) survivors, there was no significant association with all‐cause mortality for the fatigued group in multivariable analyses. Conclusion: Our study found that CRF is significantly associated with all‐cause mortality in male CRC survivors, irrespective of potential confounders. This result suggests that clinicians should increase their attention towards the recognition and treatment of CRF. Abstract : Our study found that cancer‐related fatigue is significantly associated with all‐cause mortality in male colorectal cancer survivors. This result suggests that clinicians should increase their attention towards the recognition and treatment of cancer‐related fatigue.